2014
DOI: 10.3382/ps.2013-03339
|View full text |Cite
|
Sign up to set email alerts
|

Yerba mate enhances probiotic bacteria growth in vitro but as a feed additive does not reduce Salmonella Enteritidis colonization in vivo

Abstract: Yerba mate (Ilex paraguariensis) is a tea known to have beneficial effects on human health and antimicrobial activity against some foodborne pathogens. Thus, the application of yerba mate as a feed additive for broiler chickens to reduce Salmonella colonization was evaluated. The first in vitro evaluation was conducted by suspending Salmonella Enteritidis and lactic acid bacteria (LAB) in yerba mate extract. The in vivo evaluations were conducted using preventative and horizontal transmission experiments. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
2
10
1
1
Order By: Relevance
“…Similar conclusions of finding no antagonism in vivo are noted in the study by Bratz et al [83]. Another study [79] found that the tea Yerba mate exhibited antagonistic activity in vitro but as a feed additive did not reduce S. Enteritidis colonization in vivo in broiler chickens. These studies prove that successful in vitro assays do not necessarily mean that the chosen microorganism with probiotic properties will be successful in real conditions.…”
Section: Recent Results Of Determining the In Vivo Antimicrobial Assasupporting
confidence: 83%
See 1 more Smart Citation
“…Similar conclusions of finding no antagonism in vivo are noted in the study by Bratz et al [83]. Another study [79] found that the tea Yerba mate exhibited antagonistic activity in vitro but as a feed additive did not reduce S. Enteritidis colonization in vivo in broiler chickens. These studies prove that successful in vitro assays do not necessarily mean that the chosen microorganism with probiotic properties will be successful in real conditions.…”
Section: Recent Results Of Determining the In Vivo Antimicrobial Assasupporting
confidence: 83%
“…Probiotic candidates have been accessed from very diverse habitats including faeces of breastfed human infants [65,69,80,85,95], faeces of healthy adults [9,15,65,70], faeces of elderly [81], faeces of children [25,96], breast milk [42], human saliva [52], vaginal isolates of healthy women [66,75], various fermented foods or beverages including raw or fermented milk [23,35,44], kefir [97], cheese [51,56,98], whey [99], yogurt [16,41], dahi [100,101], other dairy products [25,36,61], sourdough [102], sausages [17], fermented meat [24], kimchi [10,62], maize [25,59], fermented olives [103], Yerba mate [79], ragi [64], soy sauce [86], soil [104], as well as animal origin including rat faeces [71], geese [68], c...…”
Section: Discussionmentioning
confidence: 99%
“…Using new molecular techniques, this same study reported an increase of bacteria diversity and Lactobacillus populations when grape seed extract was included at 7.2 g/kg in the chicken diet. Yerba Mate extracts supported and increased the growth of Lactobacillus and Pediococcus and were antimicrobial against Salmonella and Campylobacter (González-Gil et al 2014). …”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…Some herbs and spices have a positive influence on feed intake due to increased palatability and, thus, improve the growth rate (Brenes and Roura, 2010;Lee at al., 2004b,c). However, some phytobiotics have a negative effect on total feed intake due to the strong flavors González-Gil et al 2014).…”
Section: Sensory Propertiesmentioning
confidence: 99%
See 1 more Smart Citation